2020
DOI: 10.1111/hel.12723
|View full text |Cite
|
Sign up to set email alerts
|

Searching for an optimal therapy for H pylori eradication: High‐dose proton‐pump inhibitor dual therapy with amoxicillin vs. standard triple therapy for 14 days

Abstract: Background & Aims We compared a high‐dose dual therapy (HDDT) with rabeprazole and amoxicillin and compared it with a standard triple therapy (STT) with rabeprazole, amoxicillin, and clarithromycin for 2 weeks for H pylori eradication in treatment naïve patients. Methods H pylori‐positive patients were randomly assigned to either a rabeparzole (Pariet) 20 mg b.i.d., amoxicillin (Ospamox) 1 g b.i.d. and clarithromycin (Klacid) 500 mg b.i.d. for 14 days or rabeprazole (Pariet) 20 mg q.i.d., amoxicillin (Ospamox)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Clarithromycin is a key antibiotic that we continue to recommend as first-line therapy. A recently published paper from our centre has shown a high success rate with 2-week STT incorporating clarithromycin which is reflective of the susceptibility of our local strains to clarithromycin ( Hwong-Ruey Leow, Chang & Goh, 2020 ). However, with the rise in resistance rates as shown in this present study, success rates of this therapy will drop in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Clarithromycin is a key antibiotic that we continue to recommend as first-line therapy. A recently published paper from our centre has shown a high success rate with 2-week STT incorporating clarithromycin which is reflective of the susceptibility of our local strains to clarithromycin ( Hwong-Ruey Leow, Chang & Goh, 2020 ). However, with the rise in resistance rates as shown in this present study, success rates of this therapy will drop in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies involving H . pylori first‐line therapy encompassed 1999 patients 5‐7,23‐25 . In the ITT analysis, the eradication rate of the DT was significantly higher than that of other regimens (89.8% vs 84.2%, OR: 1.63, 95% CI: 1.02–2.61, p = 0.04).…”
Section: Resultsmentioning
confidence: 98%
“…The current systematic reviews and meta‐analyses showed that PPI‐amoxicillin DT is not superior to other regimens, 16‐20 however, several recent studies have shown that the PPI‐amoxicillin DT administered four‐times daily can obtain a high eradication rate, 5‐7 deeming it as not just a combination of two drugs but also as a method with a pathophysiological basis to achieve satisfactory efficacy. Three main factors have been speculated to affect the efficacy of DT.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations